Kortara: The Process of Forming Acronyms on Indonesian Military Academy Corpus - Dhika JR, Vicno Triwira; Ermanto, Ermanto (Humanus, 2023)
This study aims to examine the process of forming acronyms on the Indonesian military academy corpus in KORTARA using a corpus linguistics approach. The method used is a descriptive corpus linguistic approach. The data source for this research is the Akmil blog website which is accessed through the linguistic application Korpus Nusantara (Korpus Nusantara) on the page https://korpusnusantara.fbs.unp.ac.id/. The data collection technique used in this research is the documentation technique, which analyzes the target data in the form of corpus files in KORTARA (Korpus Nusantara). This study used computational linguistic analysis techniques for the linguistic application of the KORTARA corpus (Korpus Nusantara). Based on the research that has been done, 723 acronym data were obtained on the Akmil blog website. The 723 acronyms include combining syllables (29 data), combining syllables with letters (334 data), combining letters with letters (357 data), combining syllables with words (2 data), and combining letters with words (1 data).  This study also discovered the process of forming new acronyms, in the form of combining letters with words.